Analisis Mitigasi Perubahan Iklim Melalui Peran Adat Gella di Karampuang Sinjai - Zidan Patrio; Nurizal Muhair; Djuli Harjanto; Nurhamdana; Agussalim Burhanuddin (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2023)
Forest and land use play a vital role in mitigating climate change. In Karampuang Hamlet, Sinjai Regency, South Sulawesi, customary community is under the supervision of Gella as the leader of custom who conserves their forest. This research aims to find out the role of Gella in maintaining forest environment and land based on the custom in mitigating climate change and how Gella makes policy related to climate change analyzed based on Fiedler’s Contingency Theory. This research used a qualitative approach with observation, in-depth interview, and Focus Group Discussion (FGD) being the methods of collecting data. The result of research shows that Gella plays three main roles in maintaining forest environment and land: sustainable farming-based adaptation, and advocacy and collaboration. Viewed from Fiedler’s Contingency theory, Gella plays very strong role in Karampuang community and thereby can influence decision making in the attempt of mitigating climate change. The role can be seen from three elements: leader-follower relation, task structure, and position strength. This research concludes that Gella is an ideal type of leader in the attempt of mitigating climate change.